2019
DOI: 10.1097/pec.0000000000001282
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Variation in Emergency Department Care for Children With Asthma

Abstract: In this study, children from racial/ethnic minority groups had higher odds of steroid administration and lower odds of radiological testing compared with white children. The underlying reasons for these differences are likely multifactorial, including varying levels of disease severity, health literacy, and access to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
(54 reference statements)
0
27
1
Order By: Relevance
“…Hispanic ethnicity was associated with a lower odds ratio of revisit, but not hospital readmission. Pediatric studies in the past found that more readmissions and ER visits were associated with Hispanic ethnicity, 24 , 25 , 26 , 27 , 28 , 29 but our results indicate the converse may be true for newborn infants. Simon et al 30 found that irrespective of insurance status, Latino children have lower rates of ER injury visits, perhaps due to different healthcare seeking behavior, and it is possible that similar differences in healthcare seeking behavior, cost, or access to care account for lower revisits but similar hospitalization rates in Hispanics.…”
Section: Discussioncontrasting
confidence: 86%
“…Hispanic ethnicity was associated with a lower odds ratio of revisit, but not hospital readmission. Pediatric studies in the past found that more readmissions and ER visits were associated with Hispanic ethnicity, 24 , 25 , 26 , 27 , 28 , 29 but our results indicate the converse may be true for newborn infants. Simon et al 30 found that irrespective of insurance status, Latino children have lower rates of ER injury visits, perhaps due to different healthcare seeking behavior, and it is possible that similar differences in healthcare seeking behavior, cost, or access to care account for lower revisits but similar hospitalization rates in Hispanics.…”
Section: Discussioncontrasting
confidence: 86%
“… 43 There are many examples of imaging overuse among White children, with no differences in clinical outcomes. For example, compared with non-White children, White children have higher rates of advanced imaging for abdominal pain and abdominal trauma 9 , 10 , 44 and chest radiographs for bronchiolitis, 11 asthma, 12 and chest pain. 45 Similarly, a multicenter study observed that White children with head trauma had higher rates of CT than non-White children, 46 even among those at the lowest risk for substantial injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of racial and ethnic differences in pediatric diagnostic imaging 8 , 9 , 10 , 11 , 12 have shown higher rates of selected imaging use in non-Hispanic White children compared with non-White children. However, these studies were limited in scope, focusing on a single imaging modality for a specific condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, non-White adolescents are more likely to be tested for sexually transmitted infections than White adolescents (35) and physicians are more likely to order laboratory and radiologic tests for White children in comparison to non-White children (38). White children have higher triage acuity scores than their Black counterparts for the same conditions, have shorter wait times and are less likely to leave the emergency department without being seen (39)(40)(41). Why these disparities exist is not clear.…”
Section: Discussionmentioning
confidence: 99%